DNA G-quadruplex structure participates in regulation of lipid metabolism through acyl-CoA binding protein. Issue 12 (24th June 2022) - Xiang, Lijun; Niu, Kangkang; Peng, Yuling; Zhang, Xiaojuan; Li, Xiaoyu; Ye, Ruoqi; Yu, Guoxing; Ye, Guojun; Xiang, Hui; Song, Qisheng; Feng, Qili
Abstract: G-quadruplex structure (G4) is a type of DNA secondary structure that widely exists in the genomes of many organisms. G4s are believed to participate in multiple biological processes. Acyl-CoA binding protein (ACBP), a ubiquitously expressed and highly conserved protein in eukaryotic cells, plays important roles in lipid metabolism by transporting and protecting acyl-CoA esters. Here, we report the functional identification of a G4 in the promoter of the ACBP gene in silkworm and human cancer cells. We found that G4 exists as a conserved element in the promoters of ACBP genes in invertebrates and vertebrates. The BmACBP G4 bound with G4-binding protein LARK regulated BmACBP transcription, which was blocked by the G4 stabilizer pyridostatin (PDS) and G4 antisense oligonucleotides. PDS treatment with fifth instar silkworm larvae decreased the BmACBP expression and triacylglycerides (TAG) level, resulting in reductions in fat body mass, body size and weight and growth and metamorphic rates. PDS treatment and knocking out of the HsACBP G4 in human hepatic adenocarcinoma HepG2 cells inhibited the expression of HsACBP and decreased the TAG level and cell proliferation. Altogether, our findings suggest that G4 of the ACBP genes is involved in regulation of lipid metabolism processes in invertebrates and vertebrates.